2023
DOI: 10.3389/fchem.2023.1298808
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of alginate hydrogel-based wound dressing loaded with green chemistry cerium oxide nanoparticles

Ran Zhao,
Chenyuyao Zhao,
Yi Wan
et al.

Abstract: Interactive wound dressings have displayed promising outcomes in enhancing the wound healing process. This study focuses on creating a nanocomposite wound dressing with interactive and bioactive properties, showcasing potent antioxidant effects. To achieve this, we developed cerium oxide nanoparticles utilizing curcumin as both the reducing and capping agent. Characterization techniques such as SEM, EDX, DLS, Zetasizer, FTIR, and XRD were utilized to analyze the cerium oxide nanoparticles synthesized through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…For example, animal experiments conducted by Zhao R et al on a rat whole skin wound model showed that alginate hydrogel-based wound dressings were effective in accelerating the wound healing process. This study demonstrated the safety and reliability of CeO 2 NPs (Zhao et al, 2023). However, despite the medical advantages of nanomaterials and the impressive research results, few nanomaterials can be used in clinical applications.…”
Section: Toxicity and Safety Of Ceo 2 Npsmentioning
confidence: 72%
“…For example, animal experiments conducted by Zhao R et al on a rat whole skin wound model showed that alginate hydrogel-based wound dressings were effective in accelerating the wound healing process. This study demonstrated the safety and reliability of CeO 2 NPs (Zhao et al, 2023). However, despite the medical advantages of nanomaterials and the impressive research results, few nanomaterials can be used in clinical applications.…”
Section: Toxicity and Safety Of Ceo 2 Npsmentioning
confidence: 72%